In Situ Fluorescence Microscopy Study of the Interfacial Inhomogeneity of DNA Mixed Self‐Assembled Monolayers at Gold Electrodes. Issue 3 (19th January 2015) - Meunier, Anne; Triffaux, Eleonore; Bizzotto, Dan; Buess‐Herman, Claudine; Doneux, Thomas
Abstract Mixed self‐assembled monolayers composed of a fluorescently labeled DNA and a mercaptobutanol diluent immobilized on gold electrodes were characterized by electrochemical measurements coupled with in situ fluorescence microscopy. The reductive desorption of the self‐assembled monolayers was monitored in real time through variations in the capacitance and fluorescence intensity. Desorption occurred in several steps, which was related to substrate crystallinity. Fluorescence microscopy revealed the presence of spatial heterogeneities in the form of highly fluorescent aggregates that remained at the electrode surface even after a reductive desorption step. This in situ electrofluorescence microscopy technique is useful to optimize the formation of the mixed layer to obtain a homogeneous distribution of the probes, which thus improves the efficiency of the recognition process in the development of biosensors.